A retrospective analysis of the clinical effectiveness of subcutaneously tunneled femoral vein cannulations at the bedside: A low risk central venous access approach in the neonatal intensive care unit. Issue 6 (November 2021) - Ostroff, Matthew; Zauk, Adel; Chowdhury, Sara; Moureau, Nancy; Mobley, Carly
Objective: The purpose of this retrospective analysis was to evaluate the clinical efficacy and safety of ultrasound (US)-guided, subcutaneously tunneled, femoral inserted central catheters (ST-FICCs) in the neonatal intensive care unit (NICU). Methods: Following clinical success with ST-FICCs in adults, we expanded this practice to the neonatal population. In an 18-month retrospective cohort analysis (2018–2020) of 82 neonates, we evaluated the clinical outcome for procedural success, completion of therapy, and incidence of early and late complications for insertion of US-guided ST-FICCs in the NICU. Results: Placement of ST-FICCs were successful in 100% of neonates ( n  = 82/82) with 94% to the right ( n  = 77/82) and 6% to the left common femoral veins ( n  = 5/82). Gestational age ranged 23-39 weeks with median age of 29 weeks. Birthweight ranged from 450 g to >2000 g. Weight at insertion ranged 570 to 3345 g and day of life 1 to 137, with median at day 5. Ultrasound guided femoral vein puncture was recorded on 74 patients, first attempt 63/74 (85%), second attempt 8/74 (11%) and third attempt 3/74 (4%). Catheter french used: 1.9Fr ( n  = 80/82), 2.6Fr ( n  = 1/82), and 3-Fr ( n  = 1/82). Catheter lengths were 8 to 20 cm, average 12cm. Catheter termination confirmed with posterior/anterior and lateral abdominal radiographs with inferior vena cava (IVC) ( n  = 33/82), IVC/right atrial junction ( n  = 31/82), or right atrium ( n  = 18/82). Atrial placements were retracted; no cases of malposition to the lumbar/renal/hepatic veins ( n  = 0/82). 1528 catheter days ranging 5 to 72 days (average 18). No insertion-related or post-insertion complications. All patients completed prescribed therapy with one catheter. Conclusion: Bedside placement of an ST-FICC is a safe route for central venous access in the NICU, preserving upper extremity vasculature, eliminates risks associated with sedation, fluoroscopy, tunneled and non-tunneled supra-diaphragmatic central venous insertion.